Corporate social responsibility and the nonprofit sector: exploring the common ground. Issue 9 (7th December 2020) - Valentinov, Vladislav
Abstract : Purpose: Many nonprofit missions and the goals of socially responsible corporations are often found to refer to similar moral ideals related to improving the quality of human life. To take account of this salient fact, the paper aims to theorize the functional equivalence between corporate social responsibility (CSR) and the nonprofit sector. Design/methodology/approach: The argumentative strategy is to draw on the conceptual construct of the complexity-sustainability trade-off to develop a systems-theoretic interpretation of Roger Lohmann's vision of the commons as an embodiment of collective voluntary action. Findings: The emerging conceptual imagery is that of corporations and nonprofits as social systems continually seeking to sustain themselves by processing and codifying their societal environment which includes the commons in which Lohmann took a central interest. The possible functional equivalence of corporations and nonprofits is traced back to their struggling to develop and improve their responsiveness to the respective commons. Originality/value: This argument is shown to cut across a range of issues in the modern nonprofit sector scholarship, while shedding new light on the ongoing debates on CSR and stakeholder theory.